Ghost Rider [videorecording (DVD)] - Johnson, Mark Steven, 1964-; Cage, Nicolas, 1965-; Mendes, Eva, 1974-; Elliott, Sam, 1944-; Fonda, Peter, 1940-2019 (Sony Pictures Home Entertainment, 2007)
In order to save his dying father, Johnny Blaze, a young stunt cyclist, sells his soul to Mephistopheles and sadly parts from Roxanne, the girl he loves. Years later, Johnny's path crosses again with Roxanne, who is now a reporter. He, also, crosses paths with Mephistopheles, who offers to release Johnny's soul if Johnny becomes the fabled, fiery Ghost Rider, a supernatural agent of vengeance and justice. Mephistopheles orders Johnny to defeat the despicable Blackheart, Mephistopheles's nemesis and son, who plans to displace his father and create a new hell even more terrible than the old one.